STRATEGI GASTRODIPLOMASI TEMPE MELALUI DIASPORA INDONESIA DI AMERIKA SERIKAT PADA ERA COVID-19 - Windy Utami Larasati (2023)
The era of globalization is an era where there are no more boundaries between one country and another, there are no boundaries between space and time. With the development of globalization, of course, many countries are now implementing a soft power strategy as a way to enhance cooperation and nation-branding, one of which is cultural diplomacy. Cultural diplomacy of course also consists of several types, one of which is gastrodiplomacy. Gastrodiplomacy means a process of diplomacy between one country and another through culinary arts, and the gastrodiplomacy discussed in this study is tempeh gastrodiplomacy. As we know that the COVID-19 pandemic that hit many countries in the world yesterday had a huge impact on several sectors, one of which was the culinary sector, namely tempeh, this occurred due to a decrease in soybean commodity stocks in the US. However, 2 Indonesian diaspora (Mayasari Indonesian Grill and Wiwas Tempeh) always had alternative ways to survive the COVID-19 pandemic at that time. With the support from the Indonesian Consulate General in New York, they can still introduce tempeh to the surrounding community. The results of this study indicate that the gastrodiplomacy strategy carried out by the diaspora can work very well because they have succeeded in penetrating the market and the response of the Indonesian government which tends to always support their efforts. Keywords: Gastrodiplomacy, Tempe, Nation-Branding, Diaspora, Indonesia, United States of America